Mining Social Media Data Using R and WEKA Tools - Jayaram, B. (International Journal of Psychosocial Rehabilitation, 2024)
These days, a lot of data is available in social media in various types. These data can be extracted from various sources using different application software. In this paper, I have organized my discussion as follows: first part deals with an introduction to social media processing; the second part explains how social media and machine learning are related with a detailed discussion; the third section deals with tools of machine learning (WEKA and R) and their comparison; the fourth section deals about how to extract data from social mining websites, and the last part explains about how to process social websites data with data big data tools (WEKA and R)